2017
DOI: 10.18632/oncotarget.20524
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Botch in experimental intracerebral hemorrhage in rats

Abstract: Notch1 maturation participates in apoptosis and inflammation following intracerebral hemorrhage (ICH). It has been reported that Botch bound to and blocked Notch1 maturation. Here we estimated the role of Botch in ICH-induced secondary brain injury and underlying mechanisms. Experimental ICH model was induced by autologous arterial blood injection in Sprague-Dawley rats, and cultured primary rat cortical neurons were exposed to oxyhemoglobin to mimic ICH in vitro. Specific small interfering RNAs and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous study demonstrated that overexpression of Botch in vivo alleviated neuronal apoptosis and inflammation in intracerebral hemorrhage [48]. We hypothesized that BMSCs transplantation inhibited Notch1 signaling by increasing Botch expression in brain tissue; we first detected Botch protein and mRNA levels in BMSCs, with results indicating that Botch strongly expressed in cultured BMSCs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous study demonstrated that overexpression of Botch in vivo alleviated neuronal apoptosis and inflammation in intracerebral hemorrhage [48]. We hypothesized that BMSCs transplantation inhibited Notch1 signaling by increasing Botch expression in brain tissue; we first detected Botch protein and mRNA levels in BMSCs, with results indicating that Botch strongly expressed in cultured BMSCs.…”
Section: Discussionmentioning
confidence: 91%
“…As an endogenous blocker of Notch1 receptor, Botch inhibits the S1 furin-like cleavage of Notch1, thus promoting maintenance of full-length Notch1 [46]. Recent studies reported that Botch promoted neurogenesis through antagonizing the maturation of Notch1 during neocortical development and intracerebral hemorrhage [47, 48]. However, whether Botch participates in the suppressive effects of BMSCs on Notch1 expression remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The p‐RhoA (RRID: can’t be found), MAG (RRID: AB_2042411), OMgp (RRID: AB_1587278), synaptophysin (SYP; RRID: AB_2286949) antibodies were detected at 28, 53, 20, and 35 kDa, respectively (Carlson, Henchir, & Dixon, ; Pritchard, Mir, & Dev, ; Soliman et al, ; Vose et al, ). The neuronal nuclei (NeuN; RRID: AB_2532109) recognized two bands corresponding to 48 and 50 kDa (Mei et al, ; Zhou et al, ). β‐actin (RRID: can’t be found) was detected as a 43 kDa immunoreactive band (North, Galazkiewicz, Byers, Glenney, & Small, ).…”
Section: Methodsmentioning
confidence: 99%